Novel thermal conductivity-mixing ratio-temperature mathematic model for forecasting the thermal conductivity of biodiesel-diesel-ethanol blended fuel. Issue 3 (14th September 2022) - Zhao, Zhongjin; Fashe, Li; Shuang, Wang; Zhang, Huicong; Zheng, Yuzeng; He, Xuyao; Wang, Wenchao
ABSTRACT: To explore the thermal conductivity of diesel-biodiesel-ethanol blended fuel under different temperatures and mixing ratios, three ternary blended fuels, namely, Jatropha/soybean/catering waste oil biodiesel-diesel-ethanol, were prepared. The three biodiesel components were analyzed using gas chromatography-mass spectrometry. A Hot Disk 2500S thermal constant analyzer was used to measure the thermal conductivity of the blended fuels in the temperature range of 20–60°C. Thermal conductivities of the three blended fuels increased with increase in temperature, and the three blended fuels had different thermal conductivities at the same temperature and mixing ratio. This may be attributed to the different contents of unsaturated fatty acid methyl esters in the blended fuels. The optimal mixing ratio was determined to be 80% diesel, 15% biodiesel, and 5% ethanol. Further, a thermal conductivity ( λ ) forecasting model related to temperature ( t ) and mixing ratio ( w ) was established based on experimental results, and its accuracy was evaluated using correlation coefficients and the average absolute percentage error. The value of the correlation coefficient reached 0.9700 for all three blended fuels, and the value of the average absolute percentage error was 0.2738, 0.2823, and 0.8596%, respectively. Thus, the variation of fuel thermal conductivity with temperature and mixing ratio could be accurately predicted. The findings of this study provide insights for designing thermophysical parameters of biodiesel.